2016 International Congress of Entomology 2016
DOI: 10.1603/ice.2016.107647
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacteria mediate aggregation in the German cockroach

Abstract: Aggregation of the German cockroach, Blattella germanica, is regulated by fecal aggregation agents (pheromones), including volatile carboxylic acids (VCAs). We demonstrate that the gut microbial community contributes to production of these semiochemicals. Chemical analysis of the fecal extract of B. germanica revealed 40 VCAs. Feces from axenic cockroaches (no microorganisms in the alimentary tract) lacked 12 major fecal VCAs, and 24 of the remaining compounds were represented at extremely low amounts. Olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Recently, a study showed that Enterobacteriaceae can degrade trichlorphon and conferred host insecticide resistance in B. dorsalis (Cheng et al., ). In other insects, these bacteria may contribute to nitrogen fixation (Behar et al., ), they may affect mating latency (Ben Ami et al., ) and pheromone synthesis (Wada‐Katsumata et al., ) and they may play essential role to host fitness by preventing the establishment or proliferation of pathogenic microorganism (Cirimotich et al., ; Koch & Schmid‐Hempel, ). Thus, the reduction of the Enterobacteriaceae main flora in B. dorsalis gut may result in decreased nitrogen fixation, blocked pheromone synthesis and flourishing in minor members of the gut microbiota, which then lead to various features of ecological fitness decline in sterile males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study showed that Enterobacteriaceae can degrade trichlorphon and conferred host insecticide resistance in B. dorsalis (Cheng et al., ). In other insects, these bacteria may contribute to nitrogen fixation (Behar et al., ), they may affect mating latency (Ben Ami et al., ) and pheromone synthesis (Wada‐Katsumata et al., ) and they may play essential role to host fitness by preventing the establishment or proliferation of pathogenic microorganism (Cirimotich et al., ; Koch & Schmid‐Hempel, ). Thus, the reduction of the Enterobacteriaceae main flora in B. dorsalis gut may result in decreased nitrogen fixation, blocked pheromone synthesis and flourishing in minor members of the gut microbiota, which then lead to various features of ecological fitness decline in sterile males.…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic microorganisms of animals create a complex ecosystem that is strongly connected with the biology of the host and contributes to its health (Clemente, Ursell, Parfrey, & Knight, ). Gut symbiotic microorganisms affect insects in several ways such as aiding food digestion and detoxification (Ceja‐Navarro et al., ), providing essential nutrients (Storelli et al., ), regulating development and immunity (Kwong & Moran, ; Shin et al., ), protecting against infectious pathogens (Cirimotich et al., ), influencing the central nervous system function and behaviour such as mating preference (Ben Ami, Yuval, & Jurkevitch, ; Sharon et al., ) and aggregation behaviour (Wada‐Katsumata et al., ). Whereas gut symbiotic microbiota community is tightly linked to insect host ecological fitness, the mechanism of the ecological fitness damage induced by sterile dose ionizing radiation and the possible role of gut microbiota is largely not understood.…”
Section: Introductionmentioning
confidence: 99%
“…; Engel & Moran ; Wada‐Katsumata et al . ). For many insect taxa, however, the composition, structure and function of these microbiota remain poorly understood.…”
Section: Introductionmentioning
confidence: 97%
“…However, knowledge on the biological interrelationship between the gut microbiota of BSF larvae and the microbial community over the course of BC is extremely limited. Gut microbiota of insects have different effects on the host, including the provision of necessary nutrients, stimulation of the immune system, removal of pathogenic microorganisms, sex determination and hormonal signalling and behaviours (Wada‐Katsumata et al ., ; Zheng et al ., ). Moreover, the insect gut plays a critical role in degradation of organic material (Engel and Moran, ) and various refractory matter, such as lignin (Li et al ., 2017a), polysaccharides (Yang et al ., ), and resistance genes (Wang et al ., 2017a).…”
Section: Introductionmentioning
confidence: 99%